Dialektika Tradisi Pada Komunitas Dayak Bakati’ Desa Sebunga Kabupaten Sambas - Donatianus BSEP Praptantya; Indah Listyaningrum (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2018)
This research was conducted to investigate in detail the existence of local culture (Dayak Bakati culture) and the existence of a global culture (religion) on the globalization era these days especially on the Dayak Bakati community who live in Sebunga Village, Sambas Regency, West Kalimantan. This study uses qualitative methods that emphasize the meaning of facts that occur in the field which are considered complex and dynamic. Based on the results of the research it was found that the local community who domicile in Sebunga Village was very welcome the inauguration of the cross country border posts (PLBN). The inauguration of the border gate officially making this village an official gateway for the movement of people, goods, and services so that changes quickly occurred and also it allows to accelerate the phenomenon of globalizations in their social life. That all is the response of the community as the owner local traditions, to the presence of culture and global traditions in their social lies in the contemporary era